Measurement of dijet kT in p-Pb collisions at √sNN=5.02 TeV - Adam, Jaroslav; Angelov, Venelin; Busch, Oliver; Fleck, Martin; Glässel, Peter; Klein, Jochen; Knichel, Michael Linus; Leardini, Lucia; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; et al. (Physics letters, 2015)
A measurement of dijet correlations in p-Pb collisions at sNN=5.02 TeV with the ALICE detector is presented. Jets are reconstructed from charged particles measured in the central tracking detectors and neutral energy deposited in the electromagnetic calorimeter. The transverse momentum of the full jet (clustered from charged and neutral constituents) and charged jet (clustered from charged particles only) is corrected event-by-event for the contribution of the underlying event, while corrections for underlying event fluctuations and finite detector resolution are applied on an inclusive basis. A projection of the dijet transverse momentum, kTy=pT,jetch+nesin(Δφdijet) with Δφdijet the azimuthal angle between a full and charged jet and pT,jetch+ne the transverse momentum of the full jet, is used to study nuclear matter effects in p-Pb collisions. This observable is sensitive to the acoplanarity of dijet production and its potential modification in p-Pb collisions with respect to pp collisions. Measurements of the dijet kTy as a function of the transverse momentum of the full and recoil charged jet, and the event multiplicity are presented. No significant modification of kTy due to nuclear matter effects in p-Pb collisions with respect to the event multiplicity or a PYTHIA8 reference is observed.
*ALICE Collaboration: J. Adam, V. Anguelov, O. Busch, M. Fleck, P. Glaessel, J. Klein, M.L. Knichel, L. Leardini, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, M.A. Voelkl, B. Windelband, M. Winn, A. Zimmermann [und 952 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 19.07.2021